Biosorption of copper by endophytic fungi isolated from Nepenthes ampullaria. (22nd August 2018) - Wong, C.; Tan, L.T.; Mujahid, A.; Lihan, S.; Wee, J.L.S.; Ting, L.F.; Müller, M.
Abstract: Copper (Cu) tolerance was observed by endophytic fungi isolated from the carnivorous plant Nepenthes ampullaria (collected at an anthropogenically affected site, Kuching city; and a pristine site; Heart of Borneo). The fungal isolates, capable of tolerating Cu up to 1000 ppm (11 isolates in total), were identified through molecular method [internal transcribed spacer 4+5 (ITS4+5); ITS1+NL4; β ‐tubulin region using Bt2a + Bt2b], and all of them grouped with Diaporthe, Nigrospora, and Xylaria . A Cu biosorption study was then carried out using live and dead biomass of the 11 fungal isolates. The highest biosorption capacity of using live biomass was achieved by fungal isolates Xylaria sp. NA40 (73·26 ± 1·61 mg Cu per g biomass) and Diaporthe sp. NA41 (72·65 ± 2·23 mg Cu per g biomass), NA27 (59·81 ± 1·15 mg Cu per g biomass) and NA28 (56·85 ± 4·23 mg Cu per g biomass). The fungal isolate Diaporthe sp. NA41 also achieved the highest biosorption capacity of 59·33 ± 0·15 mg g −1 using dead biomass. The living biomass possessed a better biosorption capacity than the dead biomass ( P < 0·05) and the roadside fungal strains showed higher Cu biosorption capacities using live biomass compared to the jungle fungal strains ( P < 0·05). Significance and Impact of the Study: Our study highlights that fungal biosorption capacity is highly dependent on the sampling area (roadside vs jungle) with roadside fungal strains showing significantly higher copper (Cu) biosorption capacities using living biomass compared to fungal strains originating from plants collected in virgin jungle ( P < 0·05). It also highlights that different biosorption mechanisms (alive – metabolic dependent and dead biomass – metabolic independent) result in different amounts of Cu being removed from the solutions. The living biomass possessed a better biosorption capacity than the dead biomass ( P < 0·05). Significance and Impact of the Study: Our study highlights that fungal biosorption capacity is highly dependent on the sampling area (roadside vs jungle) with roadside fungal strains showing significantly higher copper (Cu) biosorption capacities using living biomass compared to fungal strains originating from plants collected in virgin jungle ( P < 0·05). It also highlights that different biosorption mechanisms (alive – metabolic dependent and dead biomass – metabolic independent) result in different amounts of Cu being removed from the solutions. The living biomass possessed a better biosorption capacity than the dead biomass ( P < 0·05).